A Corpus – Based Rhetorical Moves of English Research Article Abstracts on Undergraduate Thesis STKIP PGRI Pacitan - Pureka, Mufida Nadira Yuni; Puspitasari, Indah (Universitas Muhammadiyah Mataram, 2024)
As we know that abstract has an important role in the research article. Besides, it has its own organizational framework. Every researcher must create an abstract after the research project was completed. This article aims to identify the rhetorical moves of English abstract articles on undergraduate theses at STKIP PGRI Pacitan. The analysis guideline was based on Hyland's theory (2004). The data were collected from 20 abstracts of published journal articles. The results revealed that all moves were appeared on the students’ abstract organization. However, it was found that the degree of occurrence or the frequency appearance was differed in every moves. The data informed that moves 3 and moves 4 were found in all students’ thesis abstracts. Moves 5 appeared in 12 students’ thesis abstracts. Then, moves 1 appeared in 8 students’ thesis abstracts and moves 2 appeared in 19 students’ thesis abstracts. The findings also revealed that there were many rhetorical organizations generated by the occurrences of moves and steps in students' abstracts. The variation moves that created by students depend on the students’ writing ability. This study can be a bridge to fill the gap in improving the quality of students’ writing, especially about abstract article.